Insolvency and debt restructuring in Islamic Finance: the need for a comprehensive model law - Oseni, Umar Aimhanosi (2013)
The skyrocketing uncertainties in the global economy have rekindled the need to examine issues relating to insolvency and debt restructuring. With a focus on Islamic financial transactions and Islamic financial institutions, this paper examines the interplay between three related concepts of insolvency, bankruptcy and debt restructuring. Balancing these three situations in time of financial distress of an Islamic financial institution requires a fair consideration of the rights of both the debtors‘ and creditors‘. In the light of this, this paper examines the current trends of insolvency and debt restructuring in the Islamic finance industry and proffers some future directions that would help reposition the industry to make it not only Sharī‗ah-compliant but also conventionally viable.